A novel approach of developing micro crystalline cellulose reinforced cementitious composites with enhanced microstructure and mechanical performance. (April 2017) - Parveen, Shama; Rana, Sohel; Fangueiro, Raul; Paiva, Maria Conceição
Abstract: This paper reports a novel approach of preparing aqueous suspensions of microcrystalline cellulose (MCC) for fabrication of cementitious composites. MCC was dispersed homogeneously in water using Pluronic F-127 as a surfactant with the help of ultrasonication process and the aqueous suspensions were added to cement/sand mixture to prepare cementitious composites. A commonly used stabilizing agent for MCC, carboxy methyl cellulose (CMC) was also used for the comparison purpose. The prepared suspensions were characterized through visual inspection, UV-Vis spectroscopy and optical microscopy. The developed composites were characterized for their bulk density, flexural and compressive properties as well as microstructure. The influence of Pluronic and CMC concentration, superplasticizer, dispersion technique and dispersion temperature on mortar's mechanical performance was thoroughly studied to find out the optimum conditions. Overall, Pluronic (with Pluronic: MCC ratio of 1:5) led to better MCC dispersion as well as dispersion stability as compared to CMC. The best mechanical performance was achieved with Pluronic in combination with superplasticizer using ultrasonication process, resulting in improvement of 106%, 31% and 66% in flexural modulus, flexural strength and compressive strengths, respectively (highest values reported till date). The bulk density and hydration of cementitious composites also improved significantly with the addition of MCC.